God in the Age of Science? A Critique of Religious Reason. By Herman Philipse - Taliaferro, Charles (The journal of theological studies, 2013)
Herman Philipse has produced a book very much in the tradition of John Mackie’s The Miracle of Theism. Philipse’s God in the Age of Science? is a sustained critique of the contemporary philosophical defence of theism, focusing largely on critically evaluating the work of Richard Swinburne. The book is not as nuanced and rigorous as Mackie’s work, probably because the scope and conclusions are more ambitious than The Miracle of Theism. Mackie held that theism is implausible, but not incoherent, whereas Philipse argues for both the implausibility and the incoherence of theism. There are three parts: ‘Natural Theology’, ‘Theism as a Theory’, and ‘The Probability of Theism’. If Philipse is correct, it is unreasonable to accept traditional forms of Christianity, Islam, and Judaism.